A kind of lychee-shaped hollow polymer microsphere and its preparation method and application
By using the combination technology of mesoporous microsphere carrier and metal copper quantum dots in oil field applications, lychee-shaped hollow polymer microspheres were prepared, which solved the shortcomings of existing microspheres in temperature resistance and salt resistance and sealing strength, and achieved more efficient oilfield deep dissection and displacement effects.
Patent Information
- Application Number
- CN202411766727.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-04
AI Technical Summary
In oilfield applications, existing polymer microspheres have problems such as poor temperature and salt resistance, easy to break and low sealing strength, which are difficult to meet the needs of deep dissection and displacement of oilfields.
Mesoporous microspheres are used as carriers, combined with metal copper quantum dots and water-soluble initiators, and litchi-like hollow polymer microspheres are prepared by reverse phase emulsion polymerization to improve their stability and elasticity.
The prepared litchi-shaped hollow polymer microspheres expand stably under high temperature and high salt conditions, have good elastic deformation ability and sealing effect, and can effectively improve crude oil recovery.
Smart Images

Figure CN119219839B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry, and particularly relates to a litchi-shaped hollow polymer microsphere and a preparation method and application thereof. Background Art
[0002] The plugging microspheres are mainly water-absorbent resin microspheres. Due to their large expansion multiple, good toughness and effective delayed expansion performance, they can migrate to deep formations with the injected water, forming high-strength plugging of large formation pores, so that subsequent injected water is diverted to areas not affected by the water flow, reducing the water output of the oil well and increasing crude oil production.
[0003] The effective period of deep profile control agent for plugging pores is related to many factors: the matching ability of profile control agent and pores, the heat resistance of profile control agent itself and reservoir channeling conditions. The polymer microsphere deep profile control agent has the characteristics of "entering, blocking and moving". While achieving deep profile control, it continuously redistributes the profile control agent, increases the profile control radius, increases the scanning area of injected water, and achieves the purpose of fluid diversion in the deep oil layer. At the same time, polymer microsphere profile control agent can improve the fluid mobility ratio and move like a piston in the formation, thereby achieving the purpose of oil displacement. However, with the increasingly harsh reservoir conditions, conventional chemically cross-linked polymer microspheres gradually reveal shortcomings such as poor temperature and salt resistance, easy shearing and crushing, and low plugging strength. Therefore, it is particularly important for the oil industry to design and synthesize polymer microspheres with better performance.
[0004] Among them, the polymer microspheres are mainly polyacrylamide microspheres. As a new type of deep-level displacement agent for reservoir development, it is widely used in major oil fields due to its excellent hydrophilicity, swelling and viscoelasticity. The particle size of the polymer microspheres with excellent performance can reach nanometer level and the size is adjustable. The microspheres can be directly added to the injection water and the produced water of the oil field. Under the injection pressure, they can absorb formation water, and after swelling with water, they can migrate in the porous medium of the reservoir and pass through the oil layer that ordinary displacement agents cannot reach, playing the role of deep displacement and having strong applicability, simple operation, convenience and environmental protection.
[0005] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, by introducing fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixing and adsorbing with the shell monomer water to prepare the core-shell microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0006] One of the technical problems to be solved by the present invention is the problem of instability and poor expansion of the microsphere system in the prior art. A lychee-shaped hollow polymer microsphere is provided. The microsphere has good stability, high elasticity, and can be controllably expanded in brine, which can meet the on-site operation requirements for improving crude oil recovery such as water plugging, deep profile adjustment and displacement in oil field production.
[0007] The technical solution for achieving the purpose of the present invention is as follows:
[0008] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0009] (1) Modifying the mesoporous microspheres with a mercaptosilane coupling agent to prepare modified mesoporous microspheres;
[0010] (2) adding the modified mesoporous microspheres to the copper quantum dot solution, uniformly dispersing by ultrasonication, and obtaining modified mesoporous microspheres loaded with copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the copper quantum dots is 1:(0.01-0.1);
[0011] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent, and a water-soluble initiator are added to water, an alkali solution is added to adjust the pH, and nitrogen is passed to remove oxygen to obtain an aqueous phase;
[0012] (4) adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase;
[0013] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-70°C for 2-4 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0014] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres are removed by solution etching to obtain lychee-shaped hollow polymer microspheres.
[0015] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing filler and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres are solid structures with large particle sizes, weak heat resistance and salt resistance. Although they have good expansion properties, they have poor deformation ability and limited oil displacement effect. Subsequently, the inventors prepared polymer solid microspheres of various morphologies. Although their plugging ability was improved to a certain extent, the microspheres had poor elastic deformation ability and limited improvement in oil displacement ability. In order to further improve the oil displacement ability of polyacrylamide microspheres, the present invention uses mesoporous microspheres as carriers, and uses metal copper quantum dots and water-soluble initiators as catalysts to prepare lychee-shaped polyacrylamide microspheres with hollow structures.
[0016] Quantum dots have a small size, and the particle size is generally 1-10nm, which is convenient for embedding into mesoporous microspheres. Mesoporous microspheres are used as core materials. Mesoporous microspheres have a large specific surface area and pore structure. The pore structure is conducive to the embedding of metal copper quantum dots and convenient for enriching metal copper quantum dots. Since there are a large number of hydroxyl groups on the surface of mesoporous microspheres, in order to prevent them from agglomerating and improve their loading efficiency for metal copper quantum dots, the present invention modifies them by using a mercaptosilane coupling agent, which reduces the surface energy of the material and improves its dispersibility on the one hand; on the other hand, the mercapto group in the coupling agent is easy to combine with the metal copper quantum dots, preventing them from being oxidized or agglomerated, and improving the stability of the metal copper quantum dots in the solvent.
[0017] Compared with copper oxide quantum dots, metal copper quantum dots are more active; and due to their large surface area to volume ratio, the copper atoms exposed on the surface can provide a large number of active sites, thereby enhancing catalytic activity. The unpaired electrons of metal copper quantum dots can be conjugated with the double bonds of acrylamide monomers, and free radicals can be generated to initiate polymerization without chemical initiators. Under heating conditions, the initiation rate is accelerated while the monomer conversion rate is also accelerated. Compared with the previous technology of loading copper oxide quantum dots with large-particle-size mesoporous microspheres and preparing microspheres with azo substances as initiators, the hollow microspheres prepared by loading copper quantum dots on mesoporous microspheres as a matrix to initiate polymerization have a smaller particle size, and the hollow structure is conducive to displacement after deformation. More importantly, metal copper quantum dots will not be etched relative to copper oxide quantum dots; while the selection of copper oxide quantum dots not only cannot play a role in initiating polymerization and cannot form a lychee-like structure, but will also be corroded by the subsequent etching solution, causing the destruction of the microsphere structure and affecting the mechanical properties of the microspheres.
[0018] Moreover, the present invention adopts the inverse emulsion polymerization method to prepare the polymer hollow microspheres, and the water-soluble initiator and the water-soluble monomer solution are uniformly dispersed in the oil phase continuous phase through the emulsification effect of the surfactant, and the polymerization is initiated in the oil-in-water reaction system through the modified mesoporous microspheres loaded with metal copper quantum dots. The polymerization process is milder than the dispersion polymerization method, and the conditions are easy to control. In this process, the water-soluble initiator in the water phase and the metal copper quantum dots in the oil phase both initiate the monomer reaction with the mesoporous microspheres as the core. On the basis of the polymerization initiated by the metal copper quantum dots on the mesoporous microspheres, the water-soluble initiator in the water phase also initiates the polymerization of the monomer on the modified mesoporous microspheres loaded with metal copper quantum dots. Due to the difference in the initiation rates of the two, the difference in the polymerization rate is caused, resulting in a lychee-like structure on the surface of the microspheres. Subsequently, hydrofluoric acid (HF) is used to react with the mesoporous microspheres to selectively etch away the template, thereby forming a lychee-like hollow structure.
[0019] Furthermore, in step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; the mass ratio of the mercaptosilane coupling agent to the mesoporous microspheres is (0.1-1): 1. An appropriate amount of mercaptosilane coupling agent not only improves the dispersion performance of the mesoporous microspheres, but also increases the loading rate of the quantum dots, which is conducive to the formation of a hollow structure.
[0020] Furthermore, in step (1), the particle size of the mesoporous microspheres is 50-300 nm, and the pore size is 10-50 nm; the mesoporous microspheres are at least one of mesoporous titanium dioxide, mesoporous zirconium dioxide, mesoporous alumina, and mesoporous silicon dioxide.
[0021] Furthermore, the specific preparation process of the modified mesoporous microspheres in step (1) is as follows: dispersing the mesoporous microspheres and the mercaptosilane coupling agent in a methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain the modified mesoporous microspheres. The mass volume ratio of the mesoporous microspheres and ammonia water is 1g: (0.5-1) mL, the ammonia water concentration is 20wt%; the heating reaction temperature is 55-65°C, and the reaction time is 3-6h.
[0022] Furthermore, in step (3), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 6-7; the cross-linking agent is N,N-methylenebisacrylamide; and the water-soluble initiator is at least one of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, and azobisisobutylimidazoline hydrochloride.
[0023] Furthermore, in step (4), the surfactant is one or both of Span-80 and Tween-80; and the organic solvent is white oil.
[0024] Furthermore, the solution used in the solution etching method in step (6) is HF solution.
[0025] Furthermore, the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.1-1): 1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is (70-80): (85-100): 1. Furthermore, the crosslinking agent is 1.8-2.2 parts, and moderate crosslinking can not only improve the strength of the hollow microspheres, but also improve the elasticity of the hollow microspheres, so that it can take into account both rigid blocking and elastic displacement capabilities.
[0026] On the other hand, the present invention also provides a lychee-shaped hollow polymer microsphere and its application as a profile control and oil displacement agent.
[0027] The polyacrylamide microspheres prepared by the present invention have the characteristics of controllable synthetic particle size, good dispersibility and swelling when in contact with water, etc., and can be directly prepared from the sewage of the oil field to obtain working fluid for injection for profile adjustment, and used in the middle and late stages of oil field development. In the process of injecting polyacrylamide microspheres, the microspheres will first enter the water flow dominant channel, and continuously move forward along the direction of small seepage resistance. When the microspheres enter the pore throats, they will block these pore throats by stacking or bridging, so that the injection pressure is increased, forcing the subsequent injection water to turn to the unaffected oil-containing area, and the injection water flows into the small pores and the area with large seepage resistance, and continuously displaces the crude oil therein. These residual oils will converge into a larger oil flow in the large pores and move toward the oil wellhead, effectively improving the injection water sweep coefficient.
[0028] More importantly, the polyacrylamide microspheres prepared by the present invention have a hollow structure inside, which greatly improves the elastic deformation ability of the microspheres. When the pressure in front of the blocked pore throat increases to a certain value, the polymer microspheres will be easily squeezed and deformed due to the extrusion effect, thereby breaking through the pore throat like an "amoeba". At this time, a certain negative pressure will be formed between the pore throat and the surrounding rocks. The injected water will carry the remaining oil quickly through the small pore throat, and the microspheres will restore their shape after passing through the pore throat and continue to migrate forward.
[0029] The hollow structure not only improves the elastic deformation ability of the microspheres, but also prevents them from absorbing water and rupturing under high temperature and high salt conditions. After the solid microspheres commonly used in the prior art absorb water and swell, when subjected to external forces, due to the solid structure inside, the inner layer presents extrusion stress, and the outer layer presents expansion tension. The microspheres are prone to stress concentration under different stresses, causing the stress in the local area to exceed its bearing capacity, resulting in rupture. The hollow structure polyacrylamide microspheres have a hollow structure inside, which can effectively absorb and disperse the expansion tension on the surface layer to prevent the microspheres from rupturing. In addition, the hollow polyacrylamide microspheres prepared by the present invention have a lychee-like morphology on the surface. Compared with the microspheres with smooth outer surfaces, it can not only avoid the expansion and rupture phenomenon after absorbing water, but also enhance the interaction force between the microspheres, and the plugging effect is better. At the same time, as the microspheres absorb water and swell, the lychee-shaped protrusions on their surface also swell, and the expanded protrusions play the role of cross-linking microspheres, which can achieve a better plugging effect, thereby improving the oil displacement efficiency.
[0030] In addition, after the mesoporous microspheres are etched away through a simple solution etching process, the quantum dot rigid particles dispersed inside the microspheres can act as rigid fillers, further dispersing the stress on the microspheres caused by water absorption and expansion, making the microspheres stable and controllably expandable in brine, thus meeting the requirements of on-site operations to enhance crude oil recovery such as water plugging, deep profile adjustment and displacement in oil field production.
[0031] Compared with the existing disclosed technology, the positive effects of the present invention are:
[0032] (1) Replacing existing solid polymer microspheres with hollow polymer microspheres can greatly improve the utilization rate of the raw materials of the profile control agent and reduce the construction cost of the polymer microspheres.
[0033] (2) The polyacrylamide microspheres prepared by the present invention have a hollow structure inside, which improves the elastic deformation ability of the microspheres; and the lychee-like morphology on the surface can achieve a better plugging effect, truly realizing the dual functions of "displacement" and "plugging" of the microspheres. The microspheres can be directly added to the injection water and the produced water of the oil field, can absorb the formation water under the injection pressure, and can migrate in the porous medium of the reservoir after swelling in water, passing through the oil layer that ordinary displacement agents cannot reach, playing the role of deep displacement and having strong applicability, simple operation, convenience and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron micrograph of the lychee-shaped hollow polymer microspheres prepared in Example 8;
[0035] Figure 2 This is a transmission electron microscopy image of the lychee-shaped hollow polymer microspheres prepared in Example 8;
[0036] Figure 3 This is a scanning electron microscope image of the hollow polymer microspheres prepared in Comparative Example 1;
[0037] Figure 4 This is a scanning electron microscope image of the hollow polymer microspheres prepared in Comparative Example 2. DETAILED DESCRIPTION
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The present invention will be further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and can implement it, but the embodiments are not intended to limit the present invention.
[0039] Example 1
[0040] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0041] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.5mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 58°C, and the reaction time is 5.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.2:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0042] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.01;
[0043] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, the pH value is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0044] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 12:4:0.5:1:8:0.3:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 70:85:1;
[0045] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 55°C for 4 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0046] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0047] Example 2
[0048] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0049] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:1mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 63°C, and the reaction time is 3.5h; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.8:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0050] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.1;
[0051] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate the water phase;
[0052] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 16:8:2.5:3:8:0.6:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:100:1;
[0053] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 70°C for 2 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0054] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0055] Example 3
[0056] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0057] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.5mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 56°C, and the reaction time is 5.2h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.1:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0058] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.09;
[0059] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, the pH value is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0060] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 16:4:2.5:1:8:0.3:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:85:1;
[0061] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 66°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0062] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0063] Example 4
[0064] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0065] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 5h; the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.7:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0066] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.07;
[0067] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, the pH value is adjusted to 7 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0068] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 15:7:2:2.4:6.5:0.5:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 77:96:1;
[0069] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 65°C for 2.8 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0070] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0071] Example 5
[0072] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0073] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.6mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 58°C, and the reaction time is 3.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.3:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0074] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.02;
[0075] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate the water phase;
[0076] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 13:5:1:1.5:5:0.4:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 72:88:1;
[0077] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 58°C for 2.4 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0078] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0079] Example 6
[0080] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0081] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 4.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.6:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0082] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.05;
[0083] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate the water phase;
[0084] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 14:6:2:2:6:0.1:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:92:1;
[0085] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0086] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0087] Example 7
[0088] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0089] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 4.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.6:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0090] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.05;
[0091] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate the water phase;
[0092] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 14:6:2:2:6:1:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:92:1;
[0093] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0094] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0095] Example 8
[0096] A method for preparing litchi-shaped hollow polymer microspheres comprises the following steps:
[0097] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 4.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.6:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0098] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.05;
[0099] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate the water phase;
[0100] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is 14:6:2:2:6:0.5:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:92:1;
[0101] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0102] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres were removed by using a 20 wt % HF solution to obtain lychee-shaped hollow polymer microspheres.
[0103] Comparative Example 1
[0104] A method for preparing hollow polymer microspheres comprises the following steps:
[0105] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 4.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.6:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0106] (2) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent N,N-methylenebisacrylamide, and a water-soluble initiator ammonium persulfate are added to water, and sodium hydroxide solution is added to adjust the pH to 6. Nitrogen is passed through to deoxygenate and obtain an aqueous phase;
[0107] (3) Adding the modified mesoporous microspheres and surfactant into the organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres is 14:6:2:2:6:0.575:1; the mass ratio of water, organic solvent and modified mesoporous microspheres is 80:92:1;
[0108] (4) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0109] (5) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres are removed by using a 20 wt % HF solution to obtain hollow polymer microspheres.
[0110] Comparative Example 2
[0111] A method for preparing hollow polymer microspheres comprises the following steps:
[0112] (1) Dispersing mesoporous microspheres and mercaptosilane coupling agent in methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain modified mesoporous microspheres; the mass volume ratio of mesoporous microspheres and ammonia water is 1g:0.8mL, and the concentration of ammonia water is 20wt%; the heating reaction temperature is 61°C, and the reaction time is 4.5h; the mercaptosilane coupling agent is 3-mercaptopropyltrimethoxysilane; the mass ratio of mercaptosilane coupling agent to mesoporous microspheres is 0.6:1; the particle size of the mesoporous microspheres is 150nm, and the pore size is 15nm; the mesoporous microspheres are mesoporous silica;
[0113] (2) adding the modified mesoporous microspheres into a chloroform solution of metal copper quantum dots having an average particle size of 3 nm, uniformly dispersing the solution by ultrasonication, and obtaining modified mesoporous microspheres loaded with metal copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the metal copper quantum dots is 1:0.575;
[0114] (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a cross-linking agent N,N-methylenebisacrylamide are added to water, the pH is adjusted to 6 by adding sodium hydroxide solution, and nitrogen is passed to deoxygenate to obtain an aqueous phase;
[0115] (4) Adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent white oil, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; the surfactant is a mixture of Span-80 and Tween-80 in a mass ratio of 2:1; the mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant and modified mesoporous microspheres loaded with metal copper quantum dots is 14:6:2:2:6:1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is 80:92:1;
[0116] (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at 62°C for 3 hours to obtain temperature-resistant and salt-resistant polymer microspheres;
[0117] (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres are removed by using a 20 wt % HF solution to obtain hollow polymer microspheres.
[0118] Performance Test:
[0119] The hollow polymer microspheres prepared in Examples 1-8 and Comparative Examples 1-2 were dispersed in simulated formation water with a mineralization of 30,000 mg / L, expanded at 80° C. for different time periods, and the expansion multiples were measured. The results are shown in Table 1.
[0120] Low permeability cores were selected for evaluation of oil displacement effect: first, the cores were saturated with simulated formation water to determine their pore volume; then, the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; hollow polymer microsphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0121]
[0122]
[0123] Depend on Figure 1 It can be seen that the present invention has prepared lychee-shaped hollow polymer microspheres. There are a large number of granular substances on the surface of the microspheres, forming a lychee-shaped shell. Compared with microspheres with smooth outer surfaces, it can not only avoid the expansion and rupture phenomenon after absorbing water, but also enhance the interaction force between the microspheres, and the blocking effect is better. At the same time, as the microspheres absorb water and expand, the lychee-shaped protrusions on their surface also expand accordingly. The expanded protrusions play the role of cross-linking the microspheres, which can achieve a better blocking effect, thereby improving the oil recovery efficiency. Figure 2 It can also be seen that the interior of the microspheres is not entirely hollow, and there are polymers that are interconnected to a certain extent. This is because during the inverse emulsion polymerization process, under the action of quantum dots, water-soluble initiators and polymerization monomers can be immersed in the pores of the mesoporous microspheres to undergo polymerization reactions. When the mesoporous microspheres are etched away, the internal polymers will exist inside the microspheres. This part of the interconnected polymers can disperse the expansion pressure inside the microspheres to a certain extent, improving the temperature and salt resistance of the microspheres. In addition, after the mesoporous microspheres are etched away by a simple solution etching process, the quantum dot rigid particles dispersed inside the microspheres can act as rigid fillers, further dispersing the stress of the microspheres due to water absorption and expansion, making the microspheres stable and controllably expandable in salt water, meeting the requirements of field operations such as water plugging, deep profile adjustment and displacement in oil field production to enhance crude oil recovery.
[0124] Depend on Figure 3-4It can be seen that in Comparative Example 1 and Comparative Example 2, no water-soluble initiator and metal copper quantum dots were added at the same time, there was no difference in polymerization rate, and the lychee-like structure could not be formed. The particle size of the prepared microspheres was relatively large, and the particle size was very uneven. One reason was due to the uneven particle size of the mesoporous microspheres, and the other reason was due to the agglomeration of the mesoporous microspheres. At the same time, the amount of metal copper quantum dots used in Comparative Example 2 was too much, and it could not further enhance the mechanical strength of the microspheres like traditional reinforcing fillers. Instead, its water absorption and swelling performance decreased, and its oil displacement capacity decreased instead of increasing. This is because there are a large number of defects such as oxides and organic matter on the surface of metal copper quantum dots. When the amount of metal copper quantum dots is too much, the surface defects in these areas will attract surrounding molecules, ions and quantum dots to form precursor substances, which will lead to the formation of aggregation and the loss of the efficacy of quantum dots. This not only leads to a reduction in the catalytic effect of quantum dots and the strengthening effect of rigid particles, but also increases the cost and affects the water absorption and swelling performance of the microspheres. More importantly, although solid microspheres have good expansion properties, their solid structure leads to poor deformation ability and difficulty in displacement, resulting in a low oil displacement rate.
[0125] It can also be seen from the data in Table 1 that the litchi-shaped hollow microspheres are more resistant to high temperature and high salt than ordinary hollow microspheres, and are not easy to break after absorbing water and swelling. Because of its hollow structure inside, it has strong elastic deformation ability and can be easily squeezed and deformed, thus breaking through the pore throat like an "amoeba". The injected water will carry the remaining oil through the small pore throat quickly. The microspheres will restore their shape after passing through the pore throat and continue to move forward, which can greatly improve the recovery rate compared to solid microspheres. It can be seen that the hollow structure not only improves the elastic deformation ability of the microspheres, but also prevents them from absorbing water and breaking under high temperature and high salt conditions. The litchi-shaped morphology of the outer layer can not only disperse stress and avoid the expansion and rupture phenomenon after absorbing water, but also enhance the interaction force between microspheres, and the plugging effect is better. At the same time, as the microspheres absorb water and expand, the litchi-shaped protrusions on their surface also expand. The expanded protrusions play the role of cross-linking the microspheres, which can achieve a better plugging effect, thereby improving the oil displacement efficiency.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing litchi-shaped hollow polymer microspheres, characterized in that: The following steps are involved: (1) Modifying mesoporous microspheres with a mercaptosilane coupling agent to prepare modified mesoporous microspheres; the particle size of the mesoporous microspheres is 50-300 nm and the pore size is 10-50 nm; (2) adding the modified mesoporous microspheres to the copper quantum dot solution, uniformly dispersing by ultrasonication, and obtaining modified mesoporous microspheres loaded with copper quantum dots after centrifugation; the mass ratio of the modified mesoporous microspheres to the copper quantum dots is 1:(0.01-0.1); (3) Under stirring conditions, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, a crosslinking agent, and a water-soluble initiator are added to water, an alkali solution is added to adjust the pH, and nitrogen is passed to remove oxygen to obtain an aqueous phase; (4) adding the modified mesoporous microspheres loaded with metal copper quantum dots and a surfactant into an organic solvent, stirring evenly, and passing nitrogen to deoxygenate to obtain an oil phase; (5) Under stirring conditions, the aqueous phase is added dropwise to the oil phase. After the addition is completed, the reaction is carried out at a temperature of 55-70°C for 2-4 hours to obtain temperature-resistant and salt-resistant polymer microspheres; (6) The mesoporous microspheres in the heat-resistant and salt-resistant polymer microspheres are removed by solution etching to obtain lychee-shaped hollow polymer microspheres.
2. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: In step (1), the mercaptosilane coupling agent is at least one of 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; and the mass ratio of the mercaptosilane coupling agent to the mesoporous microspheres is (0.1-1):
1.
3. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: The mesoporous microspheres in step (1) are at least one of mesoporous titanium dioxide, mesoporous zirconium dioxide, mesoporous alumina and mesoporous silica.
4. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: The specific preparation process of the modified mesoporous microspheres in step (1) is as follows: dispersing the mesoporous microspheres and the mercaptosilane coupling agent in a methanol solution, adding ammonia water, heating and stirring to react, and then centrifuging, washing, and drying to obtain the modified mesoporous microspheres.
5. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: In step (3), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 6-7; the cross-linking agent is N,N-methylenebisacrylamide; and the water-soluble initiator is at least one of ammonium persulfate, potassium persulfate, azobisisobutylamidine hydrochloride, and azobisisobutylimidazoline hydrochloride.
6. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: In step (4), the surfactant is one or both of Span-80 and Tween-80; and the organic solvent is white oil.
7. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: The solution used in the solution etching method in step (6) is HF solution.
8. The method for preparing litchi-shaped hollow polymer microspheres according to claim 1, characterized in that: The mass ratio of acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, crosslinking agent, surfactant, water-soluble initiator and modified mesoporous microspheres loaded with metal copper quantum dots is (12-16): (4-8): (0.5-2.5): (1-3): (4-8): (0.1-1): 1; the mass ratio of water, organic solvent and modified mesoporous microspheres loaded with metal copper quantum dots is (70-80): (85-100):
1.
9. A lychee-shaped hollow polymer microsphere, characterized in that: The lychee-shaped hollow polymer microspheres are prepared by the preparation method of any one of claims 1 to 8.
10. Use of the lychee-shaped hollow polymer microspheres according to claim 9 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots
CN115181217A
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A